Impact of percutaneous femoral arteriotomy closure using the MANTATM device on vascular and bleeding complications after transcatheter aortic valve replacement. Issue 5 (25th March 2018) - De Palma, Rodney; Settergren, Magnus; Rück, Andreas; Linder, Rikard; Saleh, Nawzad
Abstract: Objectives: To evaluate the feasibility of fully percutaneous closure using a novel collagen‐based vascular closure device after transfemoral aortic valve replacement (TAVR). Background: TAVR is utilized increasingly for the treatment of severe symptomatic aortic stenosis. Vascular complications related to access and closure dominate the adverse event profile of the procedure despite progressively reducing arteriotomy caliber. The advent of a novel collagen‐based device (MANTA TM ) and preliminary data suggest this could be used as a routine percutaneous closure device. Methods: A prospective observational study of unselected consecutive patients undergoing TAVR in a single center. Data were collected via hospital electronic records and the SWEDEHEART registry. The primary clinical outcome was closure success and time to hemostasis. Secondary outcomes included VARC‐2 defined major and minor vascular and bleeding complications within 30 days using suture‐based closure with Prostar‐XL within the same center. Results: A consecutive cohort of 346 patients underwent TAVR via the transfemoral approach. Vascular closure with MANTA TM was successful in all with a mean time to hemostasis of 42 sec (SD 115.5, range 0–600). The composite of all‐cause mortality and major complications related to the main access site was similar between the groups (1.1% vs 1.9%, P = .61). Major bleeding occurred less frequently with MANTA TM (1.1% vs 7.8%, P = .02). Conclusion: The novel use of a collagen‐based vascular closure device for large caliber arteriotomy is feasible in an unselected population undergoing transfemoral TAVR and appears efficacious compared to percutaneous suture‐based closure. These data should prompt larger studies to evaluate efficacy and safety.